Data mining applied about polygamy using sentiment analysis on Twitters in Indonesian perception - Hertina Hertina; Muhammad Nurwahid; Haswir Haswir; Hendri Sayuti; Amri Darwis; Miftahur Rahman; Rado Yendra; Muhammad Luthfi Hamzah (Bulletin of Electrical Engineering and Informatics, 2021)
Polygamy remains one of the interesting key topics in various society, especially Indonesia. Polygamy is the act of marrying multiple spouses that means having more one wife at the same time, is common case in worldwide. In this problem, the most of Muslim in Indonesia adopt Islamic law that let men to do the polygamy with certain requirements. In worldwide communities, this has been a prominent feature and has become the subject of numerous books, heated debates, journal articles, discussion papers, and so on. Furthermore, in Indonesia the polygamous marriage has recently become a heated topic. Despite controversy, Indonesia’s law, of recent, allows people for doing polygamy in certain conditions. Because the polygamy is often debated, this study focuses on assessment of Indonesian’s perceptions through sentiment analysis and would determine people’s perception about polygamy issue from 500 tweets on Twitter. To conclude, it elucidates that the polygamy in Indonesia is a normal thing and few assume the case is as negative thing.